The Lowokwaroe Prison Museum as a Historical Building in Malang City - Ate, Roni Ririn Ole; Arsyad, Muhammad Naharuddin (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
The Lowokwaroe Prison Museum is a museum that plays a significant role in preserving history and culture in Malang City. This study aims to understand how this museum contributes to the formation of the cultural identity of the Malang community and how the cultural elements in the museum can increase historical awareness among the younger generation. The background of this study is the importance of the role of museums in preserving cultural and historical heritage, as well as the challenges faced in maintaining the relevance of museums in the digital era. The method used in this study is a qualitative descriptive method with data collection through interviews, observations, and documentation studies. The results show that the Lowokwaroe Prison Museum functions not only as a place to store historical artifacts, but also as an active educational center in disseminating knowledge about the struggle for independence. The cultural elements in the museum, such as colonial architecture and a collection of artifacts reflecting the lives of prisoners, successfully create a deep and meaningful learning experience. This study concludes that the museum has an important role in building historical awareness and cultural identity of the Malang community.